2014
DOI: 10.17229/jdit.2014-0921-003
|View full text |Cite
|
Sign up to set email alerts
|

Automated synthesis of [18F]fluorocholine using a modified GE TracerLab module

Abstract: The automated radiosynthesis of [ 18 F]fluorocholine was carried out using a modified reactor design in

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 17 publications
0
4
0
Order By: Relevance
“…These low yields are an issue in our lab because it makes it difficult to make enough product to complete QC testing, and have sufficient dose remaining to complete the patient scan, as well as rendering it impossible to scan multiple patients from a single batch or distribute doses to satellite PET centers. Utilizing the same synthesis methods and CM Sep-Pak purification methods, other labs have reported this reaction to be higher yielding (>15% non-decay corrected), although residual DMAE levels were also frequently very high (>300 μg/mL) (Kryza et al, 2008), or not reported (Sperandeo et al, 2009). The low yields obtained in our lab can, we believe, be attributed to performing gas phase reactions on a synthesis module optimized for liquid phase chemistry.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations
“…These low yields are an issue in our lab because it makes it difficult to make enough product to complete QC testing, and have sufficient dose remaining to complete the patient scan, as well as rendering it impossible to scan multiple patients from a single batch or distribute doses to satellite PET centers. Utilizing the same synthesis methods and CM Sep-Pak purification methods, other labs have reported this reaction to be higher yielding (>15% non-decay corrected), although residual DMAE levels were also frequently very high (>300 μg/mL) (Kryza et al, 2008), or not reported (Sperandeo et al, 2009). The low yields obtained in our lab can, we believe, be attributed to performing gas phase reactions on a synthesis module optimized for liquid phase chemistry.…”
Section: Introductionmentioning
confidence: 96%
“…This remains the most widely used method to date, having been adapted for SPE purification, allowing automated production with cassette-based synthesis modules such as the TRACERLab MX FDG (Kryza et al, 2008; Nader and Hoepping, 2005), a TRACERlab FX FDG (Sperandeo et al, 2009), and, in our laboratory, a TRACERLab FX FN (Shao et al, 2011b). However, in our hands and on our synthesis modules this method has proven problematic, plagued by low yields (≤4%) and, despite recently published purification improvements (Slaets et al, 2010), high DMAE contamination (≤1 mg/mL) (Shao et al, 2011a; Shao et al, 2011b).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to its high positron emission abundance, low positron energy, the small ion radius and its ease of production, fluorine-18 (F-18) become the most extensively used radioisotope for PET imaging technique. In addition, the half-life of fluorine-18 is relatively long enough to allow for multistep synthesis and transportation to remote hospitals without an on-site cyclotron [9][10].…”
mentioning
confidence: 99%